2014
DOI: 10.4093/dmj.2014.38.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Diabetes Mellitus in Korean Women: Similarities and Differences from Other Racial/Ethnic Groups

Abstract: Gestational diabetes mellitus (GDM) reflects defects in insulin secretion in response to the metabolic demands of pregnancy. While GDM is increasingly common worldwide due in large part to the obesity epidemic, its frequency is relatively low in Korean women. In this report, the prevalence and risk factors for GDM, perinatal outcomes, and postpartum course are compared in non-Korean and Korean women. While Koreans and non-Koreans with GDM share pathophysiology and complications, there may be differences in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 95 publications
1
26
0
1
Order By: Relevance
“…Previous studies suggested GDM has a strong genetic basis [41]. Under the influence of environment, lifestyles, and genetic factors, the association between RBP4 and the pathophysiology of GDM might vary in different regions [42,43]. A very recent meta-analysis investigated the association between RBP4 and polycystic ovary syndrome (PCOS), which [44] seemed to support our hypothesis by demonstrating that RBP4 levels were higher in PCOS patients in Asian countries, but not in European countries.…”
Section: Discussionsupporting
confidence: 56%
“…Previous studies suggested GDM has a strong genetic basis [41]. Under the influence of environment, lifestyles, and genetic factors, the association between RBP4 and the pathophysiology of GDM might vary in different regions [42,43]. A very recent meta-analysis investigated the association between RBP4 and polycystic ovary syndrome (PCOS), which [44] seemed to support our hypothesis by demonstrating that RBP4 levels were higher in PCOS patients in Asian countries, but not in European countries.…”
Section: Discussionsupporting
confidence: 56%
“…GDM has its clinical implications for both perinatal and postpartum maternal outcomes [5]. Perinatal outcomes include preeclampsia, Cesarean section, macrosomia, neonatal hypoglycemia, and hyperbilirubinemia, of which the risk is increased in women with GDM.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Identifying the most important factors predicting GDM at a population level could aid in the primary prevention of GDM, highlighting major modifiable risk factors that are locally relevant. However, the relative importance and interaction of risk factors can differ between Asian women and other racial or ethnic groups.…”
Section: Introductionmentioning
confidence: 99%